À propos "The Gifts and the Calling of God Are Irrevocable": Eternal Law, Uncertainty, and the Providential Cunning of God - Lévy, Antoine (Journal of ecumenical studies, 2025)
, precis:, The 2015 Vatican document, “The Gifts and the Calling of God Are Irrevocable,” delivers a new approach to the dialogue between the Catholic Church and the Jewish tradition. It brings together the Christian notion of eternal Logos and the rabbinic concept of preexisting Torah, showing how the two religious traditions can be conceived of as “complementary” within a Christian theological framework. This essay raises the question of whether a reception of this new approach is possible on the Jewish side of the dialogue. After scrutinizing the argument of the Catholic document and delving into the teachings of the rabbinic tradition, the author points to the existence of two symmetrically opposite representations of the interaction among eternal Law, Christian revelation, and Israel’s Torah. He argues that the parallel development of these two mutually exclusive representations might serve one providential purpose, something reminiscent of Hegel’s theory of the “cunning of Reason.”